FPGA implementation of CPFSK modulation techniques for HF data communication - Jaswar, Fitri Dewi; Sha'ameri, Ahmad Zuri (2003)
Digital modulation based on FSK is widely used in HF data communication. This is due to simplicity in implementation by noncoherent detection and robustness due noise and phase synchronization error.Hardware based design using FF'GA can reduced system size. The proposed modulation integrates holh the transmitter and receiver modules into a single FPGA. Further reduction in components is achieved hy adopting a multiplierless and parallel algorithm at the receiver module. This is proven by comparing with conventional noncoherent detection algorithm.